2015
DOI: 10.4103/0972-124x.153482
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal health status of transport workers of a union territory in India: A cross-sectional study

Abstract: Background:Periodontal disease is one of the most prevalent dental diseases, which affects the adult population of the world, varying only in degree from mild to severe. Transport industry is considered an important pillar for socioeconomic development of any nation. The present study was carried out to assess the periodontal health status of transport workers working in Chandigarh Transport Undertaking (CTU) buses, Chandigarh (Union territory).Materials and Methods:A cross-sectional study was conducted on all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
1
4
0
1
Order By: Relevance
“…[22][23][24] Many studies among transportation workers revealed evidence of increased cigarette and alcohol consumption. 19,20 Similarly, more over half of the workers in the current study (56.4 percent) drank alcohol, but fewer workers smoked cigarettes (35.4%).…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…[22][23][24] Many studies among transportation workers revealed evidence of increased cigarette and alcohol consumption. 19,20 Similarly, more over half of the workers in the current study (56.4 percent) drank alcohol, but fewer workers smoked cigarettes (35.4%).…”
Section: Discussionmentioning
confidence: 57%
“…25,26 It's possible that this is attributable to their poorer educational attainment, longer driving experience, and regular use of alcohol and tobacco. 19 The bulk of the participants (40.2%) in a research done by Chandra et al among bank employees in Bangalore exhibited with LOA 4-5 mm. 27 Plaque, supra-gingival, and sub-gingival calculus were all found to be significant correlates with the existence of LOA in this investigation.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Responden yang menyikat gigi kurang dari 1 x sehari memiliki risiko terjadinya penyakit periodontal 2,23 kali dibanding responden yang menyikat gigi 1 kali sehari ataupun lebih. 26 Berdasarkan penelitian yang dilakukan oleh Crocombe, et al, responden yang menyikat gigi ≥ 2 kali sehari berisiko yang lebih menderita gingivitis yaitu sebesar PR = 0,89 kali dibanding responden yang menyikat gigi < 2 kali sehari. 27 Hasil penelitian menunjukkan ada hubungan antara perilaku merokok dengan terjadinya penyakit periodontal, berbeda dengan penelitian Costa, yaitu ditemukannya prevalensi responden kelompok yang merokok sebesar 45,1% memiliki risiko terjadinya periodontitis 4,25 (95% CI = 2,82-6,41) dibandingkan dengan yang bukan perokok prevalensinya 25,6%.…”
Section: Faktor-faktor Yang Berhubungan Dengan Terjadinya Penyakit Periodontalunclassified